2013
DOI: 10.1007/s11524-013-9812-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Conceptual Framework of Urban Health Observatories toward Integrating Research and Evidence into Urban Policy for Health and Health Equity

Abstract: Detailed information on health linked to geographic, sociodemographic, and environmental data are required by city governments to monitor health and the determinants of health. These data are critical for guiding local interventions, resource allocation, and planning decisions, yet they are too often non-existent or scattered. This study aimed to develop a conceptual framework of Urban Health Observatories (UHOs) as an institutional mechanism which can help synthesize evidence and incorporate it into urban pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 11 publications
1
38
0
15
Order By: Relevance
“…Improved science and methods as well as greater availability and affordability of new data collection technologies are important enabling factors for enhancing the quality of research (110). The research has occasionally been linked to decision making (4), and new models and frameworks are being considered to improve the quality of metrics in the future (13,19). A more recent review, for example, showed that 14 composite indicators relevant for urban health are available to support decision-making processes (83).…”
Section: Discussionmentioning
confidence: 99%
“…Improved science and methods as well as greater availability and affordability of new data collection technologies are important enabling factors for enhancing the quality of research (110). The research has occasionally been linked to decision making (4), and new models and frameworks are being considered to improve the quality of metrics in the future (13,19). A more recent review, for example, showed that 14 composite indicators relevant for urban health are available to support decision-making processes (83).…”
Section: Discussionmentioning
confidence: 99%
“…Para melhorar as condições de saúde nas cidades, não basta investir na ampliação do acesso a serviços de saúde. É preciso atender necessidades básicas das populações urbanas e garantir mudanças em determinantes sociais e ambientais do adoecimento 4,5,[22][23][24][25] . Ferramentas que nos possibilitem produzir informações geolocalizadas sobre a relação entre saúde e desenvolvimento local são muito necessárias para a mobilização social que leve a mais equidade 7,8,26,27 .…”
Section: Discussionunclassified
“…In 2014, the leadership of the "Health Situation Room" of the Brooklyn Hospital Center in Brooklyn, New York was added in the governance of the observatory. The framework and governance model proposed by Caiaffa et al 3 were very influential in the development of the observatory.…”
Section: Developing An Academia-based Public Health Observatorymentioning
confidence: 99%
“…In recent years, the WHO Kobe Centre has been investigating health observatories as a possible institutional mechanism for improving public health intelligence and its application in urban areas 1,2,3 .…”
Section: Introductionmentioning
confidence: 99%